A molecular brake, not a clutch, stops the Rhodobacter sphaeroides flagellar motor. - Pilizota, T; Brown, M; Leake, M; Branch, R; Berry, R; Armitage, J (2009)
Many bacterial species swim by employing ion-driven molecular motors that power the rotation of helical filaments. Signals are transmitted to the motor from the external environment via the chemotaxis pathway. In bidirectional motors, the binding of phosphorylated CheY (CheY-P) to the motor is presumed to instigate conformational changes that result in a different rotor-stator interface, resulting in rotation in the alternative direction. Controlling when this switch occurs enables bacteria to accumulate in areas favorable for their survival. Unlike most species that swim with bidirectional motors, Rhodobacter sphaeroides employs a single stop-start flagellar motor. Here, we asked, how does the binding of CheY-P stop the motor in R. sphaeroides--using a clutch or a brake? By applying external force with viscous flow or optical tweezers, we show that the R. sphaeroides motor is stopped using a brake. The motor stops at 27-28 discrete angles, locked in place by a relatively high torque, approximately 2-3 times its stall torque.